Drivers and Barriers to Use Fintech P2P Lending among MSMEs in Metro City, Lampung - Muhammad Anif Afandi; Muhammad Ridho Al Amin (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to analyse the driver and barrier factors of MSMEs intention to apply for loan at Fintech P2P Lending in Metro City, Lampung. The driver factors consisting of economic benefit, seamless transaction, and convenience as well as the barrier factors consisting of legal risk, security risk, service products, reputation, and inertia are associated with MSME intentions to apply for loan at Fintech P2P Lending using data analysis techniques in the form of Ordinary Least Square. The results of the study show that the driver factors consisting of economic benefit dan seamless transaction variables have positive and significant effect on the intention of MSMEs to apply for loan at Fintech P2P Lending. Meanwhile, the convenience variable has positive but not significant effect on the MSMEs intention to apply for loan at Fintech P2P Lending. In addition, the barrier factors which consist of the variables of security risk, service products, and reputation have positive and significant effect on the intention of MSMEs to apply for loan at Fintech P2P Lending. Meanwhile, legal risk and inertia variables have negative but significant and not significant effect respectively on the MSMEs intention to apply for loan at Fintech P2P Lending. The results of this study are useful for the Fintech P2P lending industry as an evaluation material regarding the driving and inhibiting factors to apply for loan at Fintech P2P lending as a basis for determining Fintech P2P lending business strategies.